Mechanical Properties Test and Strength Prediction on Basalt Fiber Reinforced Recycled Concrete - Min Huang; Yuru Zhao; Haonan Wang; Shihao Lin (Advances in Civil Engineering)
In order to study the mechanical properties of basalt fiber reinforced recycled concrete (BFRRC), nine groups of tests are designed with three different replacement rates of recycled aggregates (40%, 70%, and 100%) and volume fraction of basalt fibers (0.1%, 0.2%, and 0.3%). Another group of tests on ordinary concrete without fiber and recycled aggregate is used as comparison. The workability, cubic compressive strength, splitting tensile strength, and flexural strength of BFRRC are tested and analyzed. The effects of fiber content and recycled aggregate replacement ratio on the mechanical properties of concrete are studied. The strength development of fiber reinforced recycled concrete is predicted by using convolution neural network theory. The test results show that the fluidity of concrete mixtures decreases, while the cohesion and water retention are better than ordinary concrete with the increase of replacement ratio of recycled coarse aggregate and basalt fiber content. The compressive and flexural strength of recycled concrete first decrease and then increase slightly, while the splitting tensile strength of recycled concrete continue to decrease with the increase of replacement ratio of recycled aggregate. The flexural strength and splitting tensile strength of recycled concrete are obviously improved after adding basalt fiber, while the compressive strength increases first and then decreases with the increase of fiber content. A convolution neural network model for predicting the strength of basalt fiber reinforced recycled concrete is established. The predicted results are very close to the measured values and can be used as reference for the mix ratio of basalt fiber reinforced recycled concrete.